Highly Tunable, Nanomaterial‐Functionalized Structural Templating of Intracellular Protein Structures Within Biological Species - Dae‐Hyeon Song; Chang Woo Song; Seunghee H. Cho; Tae Yoon Kwon; Hoeyun Jung; Ki Hyun Park; Jiyun Kim; Junyoung Seo; Jaeyoung Yoo; Minjoon Kim; Gyu Rac Lee; Jisung Hwang; et al. (Advanced Science)
Abstract Inside living organisms, proteins are self‐assembled into diverse 3D structures optimized for specific functions. This structure‐function relationship can be exploited to synthesize functional materials through biotemplating and depositing functional materials onto protein structures. However, conventional biotemplating faces limitations due to the predominantly intracellular existence of proteins and associated challenges in achieving tunability while preserving functionality. In this study, Conversion to Advanced Materials via labeled Biostructures (CamBio), an integrated biotemplating platform that involves labeling target protein structures with antibodies followed by the growth of functional materials, ensuring outstanding nanostructure tunability is proposed. Protein‐derived plasmonic nanostructures created by CamBio can serve as precise quantitative tools for assessing target species is demonstrated. The assessment is achieved through highly tunable and efficient surface‐enhanced Raman spectroscopy (SERS). CamBio enables the formation of dense nanogap hot spots among metal nanoparticles, templated by diverse fibrous proteins comprising densely repeated monomers. Furthermore, iterative antibody labeling strategies to adjust the antibody density surrounding targets, amplifying the number of nanogaps and consequently improving SERS performance are employed. Finally, cell‐patterned substrates and whole meat sections as SERS substrates, confirming their easily accessible, cost‐effective, scalable preparation capabilities and dimensional tunability are incorporated.